The labarum of Constantine as a Charismatic Object - Pozo, Joaquin Serrano del (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This paper proposes an analysis of the labarum, a military banner introduced by Constantine the Great during his campaign against Maxentius (AD 310-312) as a "charismatic object". It briefly examines the origins of the banner, its function, and its transformations over time. The paper argues that, originally, the labarum acted as the material embodiment of Constantine’s charismatic leadership, his mystical visions and military victories. Moreover, it worked as a focus of his personal charisma and a totem to rally his supporters. In later years, the Christian interpretation of the labarum as God’s talisman gained popularity, and Constantine tried to use it to transfer his authority to his sons. After Constantine’s death, successors and usurpers copied and displayed the labarum to claim Constantine’s prestige. Yet, in this process, they weakened the charismatic aura of the banner. The Theodosian emperors of the fifth century completed this process, transforming the labarum from an exceptional talisman of war into a traditional symbol that represented the Christianised ideology of Roman imperial triumph.